National Park behavioural intention among international tourists:the combined effect of national park attractiveness, green practices, sustainability, subjective norm, perceived behavioural control, satisfaction and mobile applications / Payam Mihanyar - Mihanyar, Payam (Institute of Graduate Studies, UiTM, 2016)
Studies on destination attractiveness as the main driver to behavioural intention have been the mainstay in tourism literature. Of late, attitudes towards sustainability and green practices have emerged as critical areas in tourism development and growth. Tourists, especially those from developed countries have voiced their strong concern over environmental degradation and this has led to conservation efforts in a number of developing countries’ national parks. As such Malaysian National Parks (MNP) strive in attracting tourists from developed countries to generate more yields, which leads to natural area protection. This thesis extended the behavioural intention literature by incorporating mobile applications as another driver to behavioural intention, as tourists embrace technology, love to get connected and seek greater involvement in their tourism experience. In addition, tourism experience has been undergoing changes due to today’s mobile applications expansion, as it offer numerous means by which tourist constructs the tourism experience by learning, understanding, self-actualizing, and feeling the places visited and the cultures embedded in these places…